Lipomatous Metaplasia of the Thyroid Gland: A Clinicopathologic Review. (11th September 2019) - Solarewicz, Joanna; Reddy, Vijaya; Bitterman, Pincas; Ghai, Ritu; Gattuso, Paolo
Abstract: Objectives: Lipomatous metaplasia involving the thyroid gland is uncommon in surgical pathology and the majority of published literature is confined to single case reports. We undertook a retrospective study to assess the frequency of fat metaplasia among benign and neoplastic thyroid lesions. Methods: Surgical pathology files from 1992 to 2018 at our institution were searched for lipomatous metaplasia involving the thyroid gland. A total of 2, 018 cases of thyroid lesions after lobectomy or total thyroidectomy with or without regional lymph node sampling were identified. Patient clinical and pathologic data were reviewed. Results: The 2, 018 thyroid cases reviewed included 828 papillary carcinomas, 33 medullary carcinomas, 26 anaplastic carcinomas, 25 follicular carcinomas, 262 follicular adenomas, 422 goiters, 373 Hashimoto thyroiditis, and 49 Grave disease. Lipomatous metaplasia was recorded in 17 cases (0.8%), which included 8 males and 9 females with a mean age of 67 years (range: 55 to 82). The most common lesion containing fat metaplasia was goiter (7/422 cases, 1.7%), followed by follicular adenoma (4/262, 1.5%), papillary carcinoma (4/828, 0.5%), Hashimoto thyroiditis (1/373, 0.3%), and Grave disease (1/49, 2%). When associated with papillary carcinoma, lipomatous metaplasia was located in the surrounding benign thyroid tissue in 2/4 cases and in malignant papillary structures metastatic to neck lymph nodes in the remaining 2/4 cases. Conclusion: Lipomatous metaplasia of the thyroid gland is a rare phenomenon, present in only 17/2, 018 cases (0.8%) in our study. It was more commonly seen in reactive processes (9/844 cases, 1.1%) and follicular adenomas (4/262 cases, 1.5%). Among the 912 cases of malignant tumors, fat metaplasia was only identified in papillary carcinoma (4/828, 0.5%), half of which showed metaplasia at the metastatic site. The presence of lipomatous metaplasia in reactive as well as neoplastic lesions cannot be used as a reliable histologic feature to exclude a neoplastic process.